Study of the Potential of Rice Bran as an Anticancer: A Systematic Literature Review - Himyatul Hidayat; Adinda Khoirun Nissa; Frisa Adelia Putri; Haniatin, Khoirul; Novita Andriyani (HM Publisher, 2024)
The bioactive compounds in rice bran have various health benefits, including anticancer potential. Cancer is a disease characterized by uncontrolled cell growth. Cancer cells can originate from any cell in the body and can spread to other parts of the body. Cancer is one of the highest causes of death in the world. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding analysis of the anti-cancer potential of rice bran. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Rice bran contains various bioactive compounds, including antioxidants, anti-inflammatory, anti-proliferative, and apoptosis-inducing agents. These compounds can work together to inhibit the growth of cancer cells and prevent their spread.